Questionable people: inventing modern Jewish selves in the Russian empire, 1860-1890 - Naṭḳovits, Sveṭlanah (Judaic Traditions in Literature, Music, and Art Series, 2025)
Natkovich-Cvr Idea #1b_REV_Cropped_Flat -- Natkovich Final.